The effect of luteal phase prolongation with medroxyprogesterone acetate on endometrial thickness and pregnancy rate in women following recurrent implantation failure - Behnaz Sadeghzadeh Oskouei; Parviz Shahabi; Hossein Babaei; Azizeh Farshbaf-Khalili (Journal of Research in Clinical Medicine)
Introduction: Assisted reproductive technology (ART) is increasingly used to help infertile couples to have a child. However, less than one-third of transferred embryos result in successful implantation and live birth. Recurrent implantation failure (RIF) is an outstanding barrier to pregnancy achievement by this advanced technology. This study was conducted to evaluate the hypothesis that luteal phase prolongation would lead to endometrial thickening and decrease the RIF’s rate. Methods: This interventional study was conducted in the infertility clinic of the Alzahra Teaching Hospital and Asadabadi polyclinic, Tabriz, Iran. Sixty women, aged 20–40 years, with a history of RIF following several in vitro fertilization treatment cycles with mid-luteal progesterone levels less than 3 ng/mL, and endometrial thickness less than 8mm were recruited through the purposive sampling method. Participants were treated for six cycles with oral medroxyprogesterone acetate (MPA) tablet 5 mg/12 h initiated from the 16th day of their menstrual cycle for 20 days and evaluated for study outcomes during this course. Endometrial thickness was compared before and after MPA administration in the whole study population. The pregnancy rate was determined. Pregnancy complications and conditions were evaluated during the study. Results: Endometrial thickness was increased in patients after MPA administration (mean difference [95% CI]: 2.66 [2.43 to 2.89]; P<0.001). Overall, 80% (n=48) of participants achieved biochemical pregnancy during a 6-month treatment. Four pregnancies out of 48, were lost in different stages of pregnancy. One participant experienced gestational diabetes in the 24th week of pregnancy. No embryo-fetal abnormality was present until delivery. Conclusion: Administration of MPA following RIF induces endometrial development and facilitates embryo implantation by luteal phase prolongation which results in natural pregnancy achievement followed by timed intercourse.